2015
DOI: 10.1016/j.gca.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The fate of silicon during glass corrosion under alkaline conditions: A mechanistic and kinetic study with the International Simple Glass

Abstract: International Simple Glass -a six oxide borosilicate glass selected by the international nuclear glass community to improve the understanding of glass corrosion mechanisms and kinetics -was altered at 90°C in a solution initially saturated with respect to amorphous 29 SiO 2 . The pH 90°C , was fixed at 9 at the start of the experiment and raised to 11.5 after 209 d by the addition of KOH. Isotope sensitive analytical techniques were used to analyze the solution and altered glass samples, helping to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
158
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(169 citation statements)
references
References 70 publications
10
158
1
Order By: Relevance
“…Formation of C-S-H phases during the alteration of ISG has also been reported by Gin et al 14 and Abdelouas et al, 31 however these authors observed the precipitation of C-S-H when ISG was altered in a KOH solution at pH 11.5 14 or the formation of tobermorite (a crystalline C-S-H phase) when ISG was altered under different relative humidities. 31 In both of these cases the Si and Ca consumed in forming C-S-H must originate from the glass.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Formation of C-S-H phases during the alteration of ISG has also been reported by Gin et al 14 and Abdelouas et al, 31 however these authors observed the precipitation of C-S-H when ISG was altered in a KOH solution at pH 11.5 14 or the formation of tobermorite (a crystalline C-S-H phase) when ISG was altered under different relative humidities. 31 In both of these cases the Si and Ca consumed in forming C-S-H must originate from the glass.…”
Section: Discussionsupporting
confidence: 58%
“…Gin et al have observed the presence of a Zr-rich film on the outer surface of ISG altered at pH 11.5 in KOH solution; they suggested that this is due to the reprecipitation of less soluble components following complete glass dissolution, however they did not report the banding seen here. 14 The formation of a ZrO 2 rich layer on the surface of the zirconia containing glasses developed for the reinforcement of cements is believed to be a critical in ensuring the improved durability of these glasses in cementitious environments 34,35 although again, banding has not been reported. While ZrO 2 is generally thought to improve the durability of glasses, especially in alkaline environments, in work on nuclear waste glasses it has been concluded Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Static tests in YCWCa at 30°C showed a continuous increase of the silica concentrations up to more than 1200 mg·L -1 for SON68 [18] and even more than 3000 mg·L -1 for the ISG [19], while the glass was still dissolving. Because the glass dissolution would proceed by a dissolution/precipitation mechanism at this high pH [20], the formed layer would be less protective than a gel layer formed by condensation at near-neutral pH. It could nevertheless constitute a diffusion barrier, leading to a dissolution rate decreasing following the square root of time, as proposed for SON68 in [18].…”
Section: Resultsmentioning
confidence: 94%